Altered Mental Status and Hyperthermia in Adult Male - Sara Lozano; Leo Kobayashi (Association of American Medical Colleges, 2009)
Abstract This resource is a SIMM file featuring a 48-year-old male who has just started a weight loss program. After drinking alcoholic beverages last night (no active drug abuse) and using diphenhydramine for mild seasonal allergies, he set off on an uncharacteristic three-mile run on a humid, warm day. He has consequently developed environmental hyperthermia with confusion (exertional heat stroke) and significant dehydration causing renal and muscle dysfunction (acute renal failure and rhabdomyolysis). A SIMM program is needed to implement this resource.